The Implementation of Google Site-Assisted Differentiation Learning Model to Improve Mathematical Reasoning of Class X Senior High School - Ary Wilman Nasution; Heris Hendriana; Rudy Kurniawan; Anik Yuliani (IKIP Siliwangi, 2023)
Differentiation model learning is an effort to facilitate students' diverse or different backgrounds so that students are able to maximize their abilities. This study aims to improve students' mathematical reasoning using the google site-assisted differentiation learning model. Mathematical reasoning is one that is important for students to master, especially class X. The method in this study was quasi-experimental, with 68 students were participated in this research from SMA PGRI 31 and SMAN 1 Pangalengan. The instruments in this study were 5 questions describing mathematical reasoning. Data were analyzed using SPSS 23 to compare between conventional learning and learning using the google site-assisted differentiation model. The results show that students who have the differentiation model were better than those using conventional learning. This shows that the class using the differentiation learning model has an advantage in reasoning ability. This is because children learn according to their respective abilities because in the differentiation of the teaching provided it is adjusted to the initial ability there is yes ng children need a lot of guidance or Scaffolding, there is a little, there is no guidance so that they are able to maximize the mathematical reasoning that children have. From the results of the study it can be concluded that there is a significant difference between learning using the Google site-assisted differentiation model and conventional learning.